Analytical Chemistry Nutritional Insights: Exploring ED-XRF, LIBS, and Chemometric Techniques for Macronutrient Determination in Non-conventional Food Plants (PANC) - da Silva Rodrigues, Leticia [UNESP]; Pereira-Filho, Edenir Rodrigues; Pereira, Fabiola Manhas Verbi [UNESP] (Springer Nature, 2024)
Non-conventional food plants (PANC) warrant considerable attention in scientific research. The modern emphasis on cultivating a wholesome diet devoid of additives, preservatives, and artificial colors while being functional and requiring minimal industrial processing has steadily increased. Furthermore, personal preferences to abstain from animal products have contributed to this shift. The existing scientific literature on plant mineral composition primarily relies on rigorous acid-based techniques, oxidizing compounds, and mineralization procedures. Recognizing the nutritional potential of PANC, this study aims to explore the development of non-intrusive analytical methods that can effectively investigate and determine the mineral composition of such samples. The research focuses on using ED-XRF (energy dispersive X-ray fluorescence), LIBS (laser-induced breakdown spectroscopy), and chemometric approaches to uncover the macronutrient composition of PANC. By harnessing the potential of these techniques and integrating them with chemometric methodologies, a deeper understanding of the nutritional secrets hidden within non-conventional food plants is aimed. The outcomes of this investigation will contribute to expanding knowledge on the macronutrient profiles and potential applications of PANC in food science and nutrition.
Keywords: Chemometrics; ED-XRF; LIBS; Nutrition; PANC; Sustainability